Active Epilepsy as Indicator of Neurocysticercosis in Rural Northwest India. (7th May 2012) - Raina, Sunil Kumar; Razdan, Sushil; Pandita, K. K.; Sharma, Rajesh; Gupta, V. P.; Razdan, Shiveta
Abstract : Objective . To determine the contribution of neurocysticercosis as a cause for active epilepsy and to establish Neurocysticercosis as major definable risk of epilepsy in our setup. Methods . We conducted a door-to-door survey of 2, 209 individuals of Bhore Pind and Bhore Kullian villages in Chattah zone of district Jammu (Jumma and Kashmir, Northwest India) to identify patients with symptomatic epilepsy. Patients with active epilepsy were investigated with neuroimaging techniques to establish diagnosis of NCC (neurocysticercosis). Results . Among 25 patients with epilepsy 10(40%) had CT/MR evidence of past or recent NCC infection. This gave us the point prevalence of 4.5/1000 for Neurocysticercosis in our study population. Interpretation . The study shows a high prevalence of NCC accounting for symptomatic epilepsy in our part of India.